Integration of public art in the Malaysian urban landscape: a case study of Johor Bahru City Centre / Muhammad Falihin Jasmi - Jasmi, Muhammad Falihin (2017)
Public art is commonly located externally in public spaces and accessible for public interaction and appreciation. The present practice involves stakeholders' collaboration, celebrates local distinctiveness and contributes to a significant public realm. The contention of this thesis is the installation, locality, and rationale of public art integration in Malaysia are widely questionable, and the awareness of public art is still low despite it frequently found in the major cities. Therefore, this thesis aims to explore public art integration in urban landscape according to suitability and functionality towards a better city growth for the community in Johor Bahru City Centre. The research methodology is designed comprising combination of quantitative and qualitative methods; (i) questionnaires survey, (ii) in-depth interview, and (iii) field assessment. Results indicated that the public was unfamiliar with the term of 'public art' itself. Conversely, they acknowledged its aesthetic and functional contributions to the city and the community. The local authority representatives concurred with the public view and strongly recommend structuring a public art guideline as it will be the most efficient method towards the provision of an effective contemporary urban landscape. The findings from field assessment helped to identify the urban characteristic of Johor Bahru City Centre which in turn provided a suitability plan for public art placement that enhances city's identity, legibility, and connectivity. The research outcome is hoped to contribute towards a better understanding among the stakeholders on public art and its impacts, thus, assisting the multi-disciplinary professionals in determining the most suitable placement for public art towards a better city growth.